Assessment of bioactive compounds, nutritional composition and antioxidant activity of Malaysian young ginger (Zingiber officinale Roscoe) - Mojani, Mansooreh Sadat; Ghasemzadeh, Ali; Rahmat, Asmah; Loh, Su Peng; Ramasamy, Rajesh (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
In current work, the nutritional composition, bioactive compounds, total phenolic contents and anti-oxidant activity of young Malaysian ginger rhizome were investigated. Proximate analysis and high performance liquid chromatography (HPLC) recruited to determine nutritional composition and bioactive compounds. The total flavonoid (TF) and total phenolic contents (TPC) of ginger rhizome were determined by aluminium chloride calorimetric assay and Folin–Ciocalteau reagent, respectively. 2,2’-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging method were used to measure antioxidant capacity. The rhizome contained high moisture content and low level of carbohydrate and energy. 6-gingerol was the most abundant component in the selected ginger, and total flavonoid and phenolic content were reported to be 3.66±0.45 mg gallic acid/g and 10.22±0.87 mg quercetin/g of dry weight of rhizome, respectively. The rhizome also showed lower antioxidant activity than controls, with the IC50 value of 46.5 vs. 15.5 for α-tocopherol and 22 for BHT. The results of this study predicted that the young ginger rhizome originated from Malaysia may exhibit anti-oxidative and anti-inflammatory potentials due to high levels of gingerols, total flavonoid and phenolic compounds and antioxidant capacity.